Mutagenic activity in waste from an aluminum products factory in Salmonella/microsome assay - Varella, S. D.; Pozetti, G. L.; Vilegas, Wagner [UNESP]; Varanda, Eliana Aparecida [UNESP] (Elsevier B.V., 2004)
The mutagenic activity of waste material originating from an aluminum products factory was determined by the Salmonella/microsome assay, using the bacterial strains TA100, TA98 and YG1024. The material was obtained by sweeping the factory floor at the end of the work shift. Organic compounds were extracted by ultrasound for 30 min in dichloromethane or 70% ethanol. After evaporation of solvent, these extracts were dissolved in dimethylsulfoxide, and tested for the mutagenic activity at varying concentrations. All the extracts from the factory had mutagenic activity, especially in the YG1024 strain, suggesting the presence of aromatic amines, later confirmed by chemical analysis. The TA98 strain also showed mutagenic activity, though it did not exhibit the highest mutagenicity index observed with the YG1024 strain. In TA100, mutagenic activity was not observed. This study should serve as an alert to management and those who are occupationally exposed, and as a warning that this type of waste should not be discarded in the environment without any control. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: mutagenic activity; Ames test; industrial waste mutagenicity; occupational exposure; manufacturing aluminum